У меня в груди Анюта: рассказы и повесть / А. Д. Дорофеев - Дорофеев Александр Дмитриевич (Любимое чтение, 2008)
Экземпляры: ДО (20180212) / Инвентарный номер: 49667 / Цена: 150.70 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д69 / ББК: 84(2Рос=Рус)6-4